2020
DOI: 10.1038/s41467-020-17855-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying the effects of physical fatigue on effort-based choice

Abstract: Physical fatigue crucially influences our decisions to partake in effortful action. However, there is a limited understanding of how fatigue impacts effort-based decision-making at the level of brain and behavior. We use functional magnetic resonance imaging to record markers of brain activity while human participants engage in uncertain choices for prospective physical effort, before and after bouts of exertion. Using computational modeling of choice behavior we find that fatiguing exertions cause participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 48 publications
(157 reference statements)
6
40
1
Order By: Relevance
“…Stress and physical activity are believed to be interrelated; stress may cause muscle fatigue and reduced muscle contraction ability, while physical exercise can counter stress [22]. However, in clinical observation, fatigue may reduce people's willingness to exercise actively in a quiet state [23]. This was also observed in our OFT results; locomotor activity significantly decreased after treatment with CRS for 15 days.…”
Section: Discussionsupporting
confidence: 62%
“…Stress and physical activity are believed to be interrelated; stress may cause muscle fatigue and reduced muscle contraction ability, while physical exercise can counter stress [22]. However, in clinical observation, fatigue may reduce people's willingness to exercise actively in a quiet state [23]. This was also observed in our OFT results; locomotor activity significantly decreased after treatment with CRS for 15 days.…”
Section: Discussionsupporting
confidence: 62%
“…the more transient state that arises during the exertion of effort itself 15 ), and early commentaries suggested that lower motivation is a central mechanism that drives the experience of fatigue 2 . This idea has received renewed interest in recent times, as a result of data that have implicated neural systems classically involved in value-based decision-making in both traits 7 , 8 , 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Effort discounting tasks have become a popular paradigm to quantify the motivation of individuals to engage in goal-directed activity 16 , 19 22 . Such tasks quantify the effect of effort on reducing (or ‘discounting’) the subjective value of available rewards, which is computationally measured as the gradient of each individual’s effort discounting function 1 , 23 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…could be critical for generating feelings of effort and fatigue. 3 The concept that fatigue could be a disease entity in itself and not just a symptom of pathological /clinical conditions gained traction after acceptance of ME/CFS [meningo-encephalomyelitis/chronic fatigue syndrome] as a chronic complex systemic disease. ME/CFS has distinct diagnostic criteria, [Institute of Medicine criteria, iom.nationalacademies.org/reports/2015/me-cfs aspx]., case definition and biological abnormalities These are: post exertional malaise, unrefreshing sleep, cognitive impairment and orthostatic intolerance.…”
Section: Fatigue As a Conceptmentioning
confidence: 99%